Hemolytic Disease of the Newborn Caused by Irregular Blood Subgroup (Kell, C, c, E, and e) Incompatibilities: Report of 106 Cases at a Tertiary-Care Centre - Karagol, Belma Saygili; Zenciroglu, Aysegul; Okumus, Nurullah; Karadag, Nilgun; Dursun, Arzu; Hakan, Nilay (American Journal of Perinatology, 2012)
Objective To determine the clinical spectrum of hemolytic disease due to irregular blood subgroup incompatibility in hospitalized neonates.Study Design The medical records of the all hospitalized newborn patients diagnosed with indirect hyperbilirubinemia due to subgroup incompatibility in Kell, C, c, E, and e systems were included in the study. Data from 106 newborns with hemolytic jaundice due to irregular blood subgroups were retrospectively evaluated, and clinical and laboratory findings were compared between patients . The treatment modalities given to the patients of each subgroup types and the laboratory findings and treatment modalities of the cases according to Coombs tests results were also analyzed. Fetal affection of the hemolysis and also fetal losses due to irregular red-cell alloimmunization were not detected in prenatal course, as there was no follow-up of these pregnancies.Results The mean postnatal hospitalizing age was 6.1 ± 5.2 days after birth. The mean total bilirubin level and the mean hemoglobin value on hospitalization were 343.7 ± 63.3 µmol/L (=20.1 ± 3.7 mg/dL) and 14.9 ± 3.4 g/dL, respectively. Of 106 patients identified with irregular subgroup incompatibility, 40 infants (37.7%) were associated with C, 22 (20.8%) with c, 30 (28.3%) with E, 9 (8.5%) with e, and 5 (4.7%) with Kell subgroup system. Positive Coombs tests (either direct and/or indirect) occurred in 28.3% of the study cases. Hydrops fetalis was determined in 5 of 106 neonates (4.7%). Twenty-two of 106 (20.8%) patients required total exchange transfusion. Positive Coombs test in cases required total exchange transfusion was 63.6%.Conclusion Our data expose the magnitude and spectrum of the potential developing severe hemolytic disease and immune hydrops due to irregular subgroup incompatibility. Minor group antibody screening is recommended both in the mother and the high-risk infants with hyperbilirubinemia and hemolytic disease of the newborn.
Keywords: hyerbilirubinemia; hemolysis; blood subgroup incompatibility; Coombs test; hydrops fetalis; exchange blood transfusion; intravenous immunoglobulin; neonate